Identificación de oportunidades de mejora en el proceso de decisión de un organismo evaluador de la conformidad, mediante el método de decisión multicriterio (AHP) (2019)
In this monograph, a methodology is developed to identify opportunities for improvement in the decision process, based on the AHP (Analytical Hierarchy Process) approach, applied to a Conformity Assessment Body, whose main function are to assess compliance with certain technical regulations, according to the sector to which it belongs. As an organization that provides a service, the OEC case study, has identified problems in the delivery reports to the clients, establishing that the main gap is in the decision process, name that receives the final stage of the process, after the auditors make final delivery of the report in which they record the findings of the third party of audit. This process is not finalized in the time expected by the client and it is perceived that there are “waste” activities that needed to be eliminated to make deliveries activities to the customer.